A Comparative study to measure the horizontal condylar guidance obtained by protrusive interocclusal records and panoramic radiographic images in completely edentulous patients - Bhandari, Arjun; Manandhar, Archana; Singh, Raj Kumar; Suwal, Pramita; Parajuli, Prakash Kumar (Journal of College of Medical Sciences-Nepal, 2018)
Background & Objectives: The study was conducted with objective to compare the horizontal condylar guidance (HCG) obtained by protrusive interocclusal records and panoramic radiographic images in completely edentulous patients. Materials & Methods: The horizontal condylar guidance was measured in 25 completely edentulous patients by protrusive interocclusal records using zinc oxide eugenol paste through a face bow transfer (HanauTM Spring bow, Whip Mix Corporation, USA) to a semi-adjustable articulator (HanauTM Wide-Vue Articulator, Whip Mix Corporation, USA). In the same patients, HCG was traced in the panoramic radiograph. The angles formed by the intersection of two lines: Frankfurt’s horizontal plane and posterior slope of articular eminence was measured using protractor to represent the horizontal condylar guidance angle on each side. Results: The mean difference between the horizontal condylar guidance angles values obtained using protrusive interocclusal record and panoramic radiograph was 2.68 degrees and 3.40 degrees for the right and the left side respectively, with the panoramic radiograph values being higher. This difference between the values was found to be highly significant between the two methods for the right side (t = 2.70, p = 0.012) and left side (t = 3.69, p = 0.001). A significant positive correlation was found between the horizontal condylar guidance obtained from protrusive interocclusal record and panoramic radiograph for the right (r = 0.643, p = 0.001) and left sides (r = 0.622, p = 0.001) separately. Conclusion: The panoramic radiographic tracing can be used to calculate the mean horizontal condylar guidance in the completely edentulous patients and these values can be used to programme semi-adjustable articulators avoiding the cumbersome process of obtaining protrusive interocclusal records.